Silicon-tin-carbon composite particle, carbon-based silicon-tin-carbon composite material and preparation method thereof, pole piece and electrochemical device
Patent Information
- Application Number
- CN202411405547.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-25
Smart Images

Figure CN119517953A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-tin-carbon composite particle, a carbon-based silicon-tin-carbon composite material, a preparation method thereof, a pole piece and an electrochemical device. Background Art
[0002] Over the years, as the automotive industry's demand for lithium-ion batteries has increased significantly, the demand for high energy density and high power density of next-generation lithium-ion batteries and improved cycle performance at high current density has also increased, so a high-energy density electrode with a long cycle and long life is needed. The most promising alternatives to graphite negative electrodes are silicon-based and tin-based materials, with theoretical capacities of 4200mAh / g and 990mAh / g, respectively, and low potentials of ~0.4VvsLi / Li + and ~0.5VvsLi / Li + However, the pulverization and stratification of silicon and tin in the lithium alloy system cause huge volume changes during the charge and discharge process, which greatly limits the capacity and cycle life of the material. According to a large number of researchers, many methods have been used to overcome this defect, such as nano-based intrinsic materials (such as nanopores, fiberization, and particle nano-based), composite carbon materials, and composite metal materials and their metal oxides.
[0003] Chinese patent application CN110336015A introduces a method for preparing a carbon-coated tin and tin-iron alloy lithium-ion battery negative electrode material. Oxidized hydroxystannate iron nanoparticles are prepared with the assistance of polyvinyl pyrrolidone using hydrazine hydrate, and further coated with tris(hydroxymethyl)aminomethane and a carbon source to obtain a carbon-coated tin and tin-iron alloy lithium-ion battery negative electrode material. The first cycle capacity of the material obtained by this method reaches 1000mAh / g, and the capacity is about 500mAh / g after 50 cycles. It shows that the negative electrode material obtained by the modified method has a significant capacity advantage over the graphite negative electrode, but the advantages of the tin material have not yet been fully utilized. It can be seen that the negative electrode material obtained by this method is still not enough to support the long-term demand for electrode materials in the development of the automotive industry.
[0004] Therefore, there is an urgent need for a simple method to maximize the capacity of tin-based materials while achieving excellent electrochemical performance. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the defects of poor capacity performance and coulombic efficiency of tin-based composite materials in the prior art, and provide a silicon-tin-carbon composite particle, a carbon-based silicon-tin-carbon composite material and its preparation method, a pole piece and an electrochemical device. The carbon-based silicon-tin-carbon composite material of the present invention has better electrical conductivity and lower charge transfer internal resistance. The battery assembled from the carbon-based silicon-tin-carbon composite material has better capacity performance, cycle performance and coulombic efficiency. The preparation method of the silicon-tin-carbon composite particle and the carbon-based silicon-tin-carbon composite material of the present invention is simple, highly practical, and easy to industrialize.
[0006] The present invention adopts the following technical solutions to solve the above technical problems.
[0007] The present invention provides a carbon-based silicon-tin-carbon composite material, which comprises a plurality of silicon-tin-carbon composite particles dispersed in a carbon substrate; the silicon-tin-carbon composite particles comprise a shell layer and tin-containing particles and nano-silicon particles encapsulated in the shell layer;
[0008] The shell layer includes a tin-containing carbon layer.
[0009] In the present invention, the tin-containing particles may be one or more of nano-tin particles, tin oxide particles and stannous oxide particles.
[0010] In the present invention, the silicon content in the silicon-tin-carbon composite particles can be 10%-40%, preferably 16%-35%, for example, 33.8%, 24.1%, 23.6%, 23.2%, 22.8%, 22.4%, 22.2%, 22.1%, 21.9%, 21.8%, 21.5%, 21.4%, 21.1%, 20.9%, 20.8%, 20.7%, 19.9%, 19.3% or 18.1%.
[0011] In the present invention, the tin content in the silicon-tin-carbon composite particles may be 30%-60%, preferably 35%-55%, for example, 51.8%, 51.4%, 50.3%, 50.2%, 49.1%, 48.6%, 48.2%, 47.3%, 47.1%, 47.0%, 46.3%, 46.0%, 45.8%, 45.7%, 45.6%, 44.8%, 44.7%, 44.3%, 44.2%, 43.4% or 39.4%.
[0012] In the present invention, the carbon content in the silicon-tin-carbon composite particles may be 10%-30%, preferably 15%-25%, for example, 22.7%, 21.8%, 20.7%, 20.5%, 20.1%, 19.8%, 19.7%, 19.2%, 18.9%, 18.3%, 18.1%, 17.9%, 17.8%, 17.7% or 17.6%.
[0013] In the present invention, the oxygen content in the silicon-tin-carbon composite particles may be 4%-20%, preferably 6%-15%, for example, 14.1%, 12.9%, 12.7%, 12.3%, 11.9%, 11.7%, 11.2%, 10.8%, 10.4%, 9.9%, 9.8%, 9.7%, 9.3%, 8.8%, 8.3%, 8.2% or 7.5%.
[0014] The content of each element mentioned above represents the percentage of the mass of each element to the mass of the silicon-tin-carbon composite particles.
[0015] In the present invention, the shell layer is preferably a heteroatom-doped tin-containing carbon layer.
[0016] The type of the heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen.
[0017] Wherein, in the silicon-tin-carbon composite particles, the content of the heteroatoms may be 0.01%-2%, preferably 0.05%-1.5%, such as 1.00%, 0.09%, 0.08% or 0.07%. The content of heteroatoms indicates the percentage of the mass of the heteroatoms to the mass of the silicon-tin-carbon composite particles.
[0018] In the present invention, the structure of the silicon-tin-carbon composite particles preferably also includes any one of the following situations:
[0019] (1) The shell layer further includes a second shell layer, the second shell layer includes a silicon film layer, and the second shell layer is coated on the surface of the tin-containing carbon layer;
[0020] (2) the shell layer further includes a second shell layer, the second shell layer includes a porous carbon layer, and the second shell layer is coated on the surface of the tin-containing carbon layer;
[0021] (3) The shell layer further includes a second shell layer and a third shell layer, the second shell layer includes a silicon membrane layer, and the third shell layer includes a porous carbon layer, and the second shell layer and the third shell layer are sequentially coated on the surface of the tin-containing carbon layer.
[0022] The present invention provides a method for preparing the carbon-based silicon-tin-carbon composite material as described above, which comprises the following steps: ball milling and pyrolyzing the silicon-tin-carbon composite particles and a carbon source B.
[0023] In the present invention, the type of the carbon source B is preferably sugar, more preferably one or more of sucrose, maltose and fructose, such as sucrose.
[0024] In the present invention, the mass ratio of the silicon-tin-carbon composite particles to the carbon source B may be (0.5-2):1, for example, 1:1.
[0025] In the present invention, when the silicon-tin-carbon composite particles and the carbon source B are ball-milled, the ball-to-material ratio can be (30-50):1, for example, 50:1. The ball milling speed can be 350-550 r / min, for example, 350 r / min. The ball milling time can be 1-3 h, for example, 2 h.
[0026] In the present invention, the pyrolysis of the silicon-tin-carbon composite particles and the carbon source B is preferably carried out under an inert atmosphere. The inert atmosphere is preferably argon, nitrogen, helium or neon, such as nitrogen. The pyrolysis temperature may be 350-700°C, such as 550°C. The pyrolysis time may be 2-5h, such as 3h. The rate of heating to the pyrolysis may be 5-15°C / min, such as 10°C / min.
[0027] The present invention also provides a method for preparing silicon-tin-carbon composite particles, which comprises the following steps: coating a carbon source comprising a tin-containing substance on the surface of a "mixture of a tin source and a silicon source", and performing a carbonization treatment to obtain the silicon-tin-carbon composite particles.
[0028] In the present invention, the tin source is preferably an organic tin source, such as a conventional tin-containing organic compound in the art. The type of the tin source is preferably one or more of tributylphenyltin, tetraphenyltin, phenylacetyl tributyltin and dibutyldiphenyltin, such as tributylphenyltin.
[0029] In the present invention, the silicon source may be a conventional silicon-containing material in the art, preferably silicon powder and / or silicon oxide powder. The D50 of the silicon source may be 20-60 nm, for example 25 nm.
[0030] In the present invention, the molar ratio of the tin source to the silicon source may be (0.8-3):1, preferably (1-2):1, for example 1.6:1.
[0031] In the present invention, the tin-containing substance may be a conventional tin-containing substance in the art, preferably one or more of anhydrous tin chloride, stannous chloride, stannous sulfate and an organic acid / tin complex, such as anhydrous tin chloride and / or an organic acid / tin complex.
[0032] Wherein, when the tin-containing substance is an organic acid / tin complex, the method for preparing the organic acid / tin complex preferably comprises the following steps: reacting an organic acid solution with an inorganic tin source to obtain an organic acid / tin complex.
[0033] The type of organic acid in the organic acid solution may be conventional in the art, preferably one or more of citric acid, tartaric acid, malic acid and lactic acid, such as citric acid.
[0034] The inorganic tin source may be any conventional source in the art, and is preferably one or more of anhydrous tin chloride, stannous chloride and stannous sulfate, such as anhydrous tin chloride.
[0035] In the organic acid solution, the molar concentration of the organic acid may be 0.22-0.26 mol / L, for example 0.25 mol / L.
[0036] The molar ratio of the organic acid to the inorganic tin source in the organic acid solution may be 1:(2.08-2.8), preferably 1:(2.2-2.5), for example 1:2.33.
[0037] The reaction process generally includes a catalyst. The catalyst is preferably added dropwise to the mixture of the organic acid solution and the inorganic tin source. The catalyst addition time may be 20-40 min. The catalyst may be a conventional alkaline solution in the art, preferably one or more of a sodium hydroxide solution, a potassium hydroxide solution, a calcium hydroxide solution, a sodium bicarbonate solution and a sodium carbonate solution, such as a sodium hydroxide solution. The concentration of the alkaline solution may be 1-5 mol / L, such as 2 mol / L.
[0038] The pH value of the reaction system is preferably monitored during the reaction. The pH value of the reaction system is preferably not more than 12, for example 5-12.
[0039] The reaction is preferably carried out under an inert atmosphere, preferably nitrogen.
[0040] After the reaction, the steps of washing and drying are generally included. The washing can be performed with water or ethanol. The drying operation can be conventional in the art, for example, drying in a vacuum drying oven at 70-90° C. for 24 hours.
[0041] In the present invention, the type of the carbon source can be conventional in the art, preferably phenolic resin and / or asphalt, more preferably surfactant-fixed phenolic resin, and even more preferably surfactant-fixed tin-containing phenolic resin.
[0042] Wherein, when the type of the carbon source is phenolic resin, the preparation method of the carbon source including the tin-containing substance preferably includes the following steps: polymerizing the tin-containing substance, formaldehyde and resorcinol. The molar ratio of the tin-containing substance to the resorcinol may be (0.5-2.5):1, preferably (1-2):1, for example, 1.6:1. The molar ratio of the formaldehyde to the resorcinol may be (333-3000):1, for example, 1000:1. The temperature of the polymerization reaction may be 80-100°C, for example, 85°C. The time of the polymerization reaction may be 2-6h, for example, 3h. A catalyst is generally added during the polymerization reaction. The catalyst may be an alkaline solution, such as a sodium carbonate solution, a sodium hydroxide solution or a sodium citrate solution. After the polymerization reaction and before the carbonization treatment, it is preferably further included to dry. Wherein, the drying operation may be conventional in the art, such as freeze drying or supercritical drying. The freeze drying temperature may be -30 to -80°C, for example, -60°C. The freeze drying time may be 3-7 hours, for example 4 hours. The supercritical drying temperature may be 10-40° C., for example 20 or 30° C. The supercritical drying time may be 1-3 hours, for example 1.5 or 2 hours. During the supercritical drying, the system pressure may be 10-15 kPa, for example 10 kPa.
[0043] Wherein, when the type of the carbon source is a phenolic resin fixed by a surfactant, the preparation method of the carbon source of the tin-containing substance preferably comprises the following steps: subjecting a surfactant, a tin-containing substance, formaldehyde and resorcinol to a polymerization reaction. The surfactant may be one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, such as hexadecyltrimethylammonium bromide. The molar ratio of the surfactant to the resorcinol may be (0.2-0.8):1, preferably (0.4-0.6):1, for example 0.492:1.
[0044] In the present invention, the carbon source preferably includes heteroatom doping.
[0045] The heteroatom may be one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen. When the heteroatom is nitrogen, the nitrogen source may be a nitrogen-containing substance, preferably one or more of p-nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile), such as triethylamine.
[0046] The molar ratio of the heteroatom to the tin source may be 1:(60-100), preferably 1:(70-90), for example 1:80.
[0047] In the present invention, the carbonization treatment is preferably carried out under an inert atmosphere, and the inert atmosphere is preferably nitrogen or argon.
[0048] In the present invention, the temperature of the carbonization treatment may be 550-850°C, for example 600°C.
[0049] In the present invention, the carbonization treatment time may be 2-6 hours, for example 3 hours.
[0050] In the present invention, the carbonization treatment preferably further comprises washing and drying steps. The washing may be performed with water or ethanol. The drying operation may be conventional in the art, for example, drying in a vacuum drying oven at 70° C. for 8 hours.
[0051] In the present invention, the method for preparing the silicon-tin-carbon composite particles preferably further comprises any one of the following steps:
[0052] (1) ball milling and pyrolyzing the particles obtained after the carbonization treatment and the silane coupling agent;
[0053] (2) ball-milling and pyrolyzing the particles and sugars obtained after the carbonization treatment;
[0054] (3) ball-milling the particles obtained after the carbonization treatment and a silane coupling agent to obtain composite particles A; and ball-milling and thermally decomposing the composite particles A and sugars.
[0055] The silane coupling agent is preferably one or more of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(β-methoxyethoxy)silane and methacryloxysilane, such as vinyl triethoxysilane.
[0056] The mass ratio of the particles obtained after the carbonization treatment to the silane coupling agent may be (10-22):1, preferably (12-18):1, for example 16:1.
[0057] When the particles obtained after the carbonization treatment and the silane coupling agent are ball-milled, the ball-to-material ratio may be (30-50):1, for example, 50:1. The speed of the ball milling may be 550-800 r / min, for example, 650 r / min. The ball milling time may be 4-8 h, for example, 6 h.
[0058] Wherein, when the particles and silane coupling agent obtained after the carbonization treatment are pyrolyzed, it is preferably carried out under an inert atmosphere. The inert atmosphere is preferably argon, nitrogen, helium or neon, such as nitrogen. The temperature of the pyrolysis may be 350-700°C, such as 550°C. The time of the pyrolysis may be 2-5h, such as 3h. The rate of heating to the pyrolysis may be 5-15°C / min, such as 10°C / min.
[0059] The sugars are a general term for polyhydroxy aldehydes or polyhydroxy ketones and their condensation products and certain derivatives, generally composed of three elements: carbon, hydrogen and oxygen, preferably one or more of sucrose, maltose and fructose, such as sucrose.
[0060] Wherein, the mass ratio of the particles obtained after the carbonization treatment to the sugar may be (0.5-2):1, for example 1:1.
[0061] When the particles obtained after the carbonization treatment and the sugar are ball-milled, the ball-to-material ratio may be (30-50):1, for example, 50:1. The speed of the ball milling may be 350-550 r / min, for example, 350 r / min. The ball milling time may be 1-3 h, for example, 2 h.
[0062] Wherein, when the particles and sugars obtained after the carbonization treatment are pyrolyzed, it is preferably carried out under an inert atmosphere. The inert atmosphere is preferably argon, nitrogen, helium or neon, such as nitrogen. The temperature of the pyrolysis may be 350-700°C, such as 550°C. The time of the pyrolysis may be 2-5h, such as 3h. The rate of heating to the pyrolysis may be 5-15°C / min, such as 10°C / min.
[0063] The present invention provides a silicon-tin-carbon composite particle, which is prepared by the above-mentioned method for preparing the silicon-tin composite particle.
[0064] The present invention also provides a pole piece, which includes the silicon-tin-carbon composite particles or the carbon-based silicon-tin-carbon composite material as described above.
[0065] The present invention also provides an electrochemical device, which comprises the pole piece as described above.
[0066] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0067] The reagents and raw materials used in the present invention are commercially available.
[0068] The positive and progressive effects of the present invention are:
[0069] The carbon-based silicon-tin-carbon composite material of the present invention includes silicon-tin-carbon composite particles, which encapsulate silicon particles and tin-containing particles in a tin-containing carbon layer, thereby avoiding volume expansion of the battery assembled therewith during the charge and discharge process and ensuring capacity stability; at the same time, the presence of the tin-containing particles improves the electronic conductivity of the obtained composite material, so that the battery assembled with the carbon-based silicon-tin-carbon composite material has better capacity performance, cycle performance and coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 Schematic diagram of the cross-sectional structure of the silicon-tin-carbon composite particles prepared in Example.
[0071] Figure 2 Schematic diagram of the cross-sectional structure of the carbon-based silicon-tin-carbon composite material prepared in the embodiment.
[0072] Figure 3 Schematic diagram of the cycle performance of the carbon-based silicon-tin-carbon composite material prepared in Example 1.
[0073] Figure 4 Schematic diagram of the rate performance of the carbon-based silicon-tin-carbon composite material prepared in Example 1.
[0074] Description of reference numerals:
[0075] 1-tin-containing particles; 2-nano silicon particles; 3-heteroatom-doped tin carbon layer; 4-silicon film layer; 5-porous carbon layer; 6-carbon substrate. DETAILED DESCRIPTION
[0076] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0077] Example 1
[0078] (1) A surfactant-fixed tin-containing phenolic resin was coated on the surface of "tributylphenyltin (0.8 mmol) and silicon powder (0.5 mmol, D50 is 25 nm)", carbonized at 550°C for 3 h in an argon atmosphere, and then repeatedly rinsed with water and ethanol, and dried in vacuum at 70°C for 8 h.
[0079] Wherein, the preparation method of the tin-containing phenolic resin fixed by a surfactant is:
[0080] Mix citric acid (33.9 mmol) and deionized water (135 mL), stir until completely dissolved (the molar concentration of the citric acid solution is 0.25 mol / L), and then add anhydrous tin chloride (79.1 mmol) to form a mixture. Stir the mixture for 20 minutes to ensure complete dissolution of the anhydrous tin chloride, then drop a 2 mol / L sodium hydroxide solution (prepared using 67.5 mL deionized water) into the mixture, and continue the reaction at 60-80°C for 20 minutes under a nitrogen atmosphere, keeping the pH value of the system at 5-12. Filter the resulting precipitate, then rinse it repeatedly with water and ethanol, and dry it overnight under vacuum at 70°C to obtain a citric acid / tin complex;
[0081] Hexadecyltrimethylammonium bromide (0.246mmol) and 0.8mmol of citric acid / tin complex were mixed and ultrasonically dispersed to form spherical micelles to fix the citric acid / tin complex. A mixture of 0.01mmol triethylamine, resorcinol (R, 0.5mmol), formaldehyde (F, 0.5mol) and sodium carbonate (0.03mmol) was added and stirred continuously to obtain a surface-stabilized sol. Subsequently, tributylphenyltin (0.8mmol) and silicon powder (0.5mmol, D50 is 25nm) were added and dispersed uniformly to obtain a surfactant-stabilized core-shell colloid. The core-shell colloid was then polymerized at 85°C for 3h to ensure that a sol polymer with a cross-linked structure was obtained, and after freeze-drying at -60°C for 4h, a surfactant-fixed tin-containing phenolic resin was obtained.
[0082] (2) Vinyl triethoxysilane and the particles obtained in step (1) are placed in a ball mill at a mass ratio of 5:80, a ball-to-material ratio of 50:1, a ball milling speed of 650 r / min, and a ball milling time of 6 hours to obtain composite particles A. The obtained composite particles A are mixed with sucrose at a mass ratio of 1:1 and placed in a ball mill at a ball-to-material ratio of 50:1, a ball milling speed of 350 r / min, and after ball milling for 2 hours, placed in a horizontal tube furnace, heated to 550°C at a heating rate of 10°C / min under argon protection, and kept at a constant temperature for 3 hours to ensure full polymerization of the material. Then cooled to room temperature, ultrasonically dispersed for 40 minutes to make it uniform, and a carbon-based silicon-tin-carbon composite material can be obtained.
[0083] Example 2
[0084] The difference from Example 1 is that in step (1), citric acid is replaced by lactic acid.
[0085] Example 3
[0086] The difference from Example 1 is that in step (1), anhydrous tin chloride is replaced by stannous chloride.
[0087] Example 4
[0088] The difference from Example 1 is that in step (1), 14 g (53.7 mmol) of anhydrous tin chloride is added.
[0089] Example 5
[0090] The difference from Example 1 is that in step (1), sodium hydroxide is replaced by potassium hydroxide.
[0091] Example 6
[0092] The difference from Example 1 is that in step (1), hexadecyltrimethylammonium bromide is replaced by alkyldimethylbenzylammonium bromide.
[0093] Example 7
[0094] The difference from Example 1 is that the amount of citric acid / tin complex added in step (1) is 1 mmol.
[0095] Example 8
[0096] The difference from Example 1 is that in step (1), triethylamine is replaced by melamine.
[0097] Example 9
[0098] The difference from Example 1 is that in step (1), the molar ratio of resorcinol to formaldehyde is 0.5 mmol:0.8 mol.
[0099] Example 10
[0100] The difference from Example 1 is that in step (1), tributylphenyltin is replaced by tributyltin phenylacetylene.
[0101] Embodiment 11
[0102] The difference from Example 1 is that in step (1), silicon powder is replaced by silicon oxide powder.
[0103] Example 12
[0104] The difference from Example 1 is that in step (1), the molar ratio of tributylphenyltin to silicon powder is 0.8 mmol:1 mmol.
[0105] Embodiment 13
[0106] The difference from Example 1 is that the drying method in step (1) is replaced by freeze drying with CO 2 Supercritical drying, temperature 20℃, pressure 10kPa, drying time 1.5h.
[0107] Embodiment 14
[0108] The difference from Example 1 is that the polymerization temperature in step (1) is 90°C.
[0109] Embodiment 15
[0110] The difference from Example 1 is that the carbonization treatment temperature in step (1) is 600°C.
[0111] Example 16
[0112] The difference from Example 1 is that the mass ratio of vinyltriethoxysilane in step (2) to the material obtained in step (1) is 5:85.
[0113] Embodiment 17
[0114] The difference from Example 1 is that in step (2), vinyltriethoxysilane is replaced by vinyltrimethoxysilane.
[0115] Embodiment 18
[0116] The difference from Example 1 is that when preparing the composite material A in step (2), the ball milling speed is 600 r / min.
[0117] Embodiment 19
[0118] The difference from Example 1 is that in step (2), when the mixture is ball-milled with sucrose, the ball-milling speed is 400 r / min.
[0119] Embodiment 20
[0120] The difference from Example 1 is that the pyrolysis temperature in step (2) is 600°C.
[0121] Embodiment 21:
[0122] The difference from Example 1 is that in step (2), the mass ratio of vinyltriethoxysilane to the material obtained after carbonization treatment is 20:80.
[0123] Embodiment 22:
[0124] The difference from Example 1 is that the polymerization temperature in step (1) is 150°C.
[0125] Embodiment 23:
[0126] The difference from Example 1 is that there is only step (1).
[0127] Comparative Example 1:
[0128] The difference from Example 1 is that it is pure silicon powder.
[0129] Comparative Example 2:
[0130] The difference from Example 1 is that it is pure tin powder
[0131] Comparative Example 3:
[0132] The difference from Example 1 is that only an organic acid / tin complex is used.
[0133] Effect Example 1
[0134] Figure 1 Figure 1 is a schematic diagram of the cross-sectional structure of the silicon-tin-carbon composite material. Figure 1It can be seen that the silicon-tin-carbon composite material includes a shell layer and tin-containing particles 1 and nano-silicon particles 2 encapsulated in the shell layer; the shell layer includes a heteroatom-doped tin-containing carbon layer 3, a second shell layer and a third shell layer, the second shell layer includes a silicon film layer 4, and the third shell layer includes a porous carbon layer 5, and the second shell layer and the third shell layer are sequentially coated on the surface of the heteroatom-doped tin-containing carbon layer.
[0135] Figure 2 Schematic diagram of the cross-sectional structure of the carbon-based silicon-tin-carbon composite material prepared in the embodiment. Figure 2 It can be seen that the carbon-based silicon-tin-carbon composite material includes a carbon substrate and a silicon-tin-carbon composite material, the silicon-tin-carbon composite material is dispersed in the carbon substrate 6, the silicon-tin-carbon composite material includes a shell layer and tin-containing particles 1 and nano-silicon particles 2 encapsulated in the shell layer; the shell layer includes a heteroatom-doped tin-containing carbon layer 3, a second shell layer and a third shell layer, the second shell layer includes a silicon film layer 4, the third shell layer includes a porous carbon layer 5, and the second shell layer and the third shell layer are sequentially coated on the surface of the heteroatom-doped tin-containing carbon layer.
[0136] XRF was used to test the element content in the carbon-based silicon-tin-carbon composite material prepared by the present invention. The test method was microwave digestion. The carbon-based silicon-tin-carbon composite material prepared in the embodiment or comparative example was pre-treated by mixing 2±0.05g of stearic acid and 6±0.5g of the carbon-based silicon-tin-carbon composite material and grinding them, then pressing them into tablets, and then TM The test was carried out in 200 equipment; the test conditions: the air pressure was 2.5MPa.
[0137] The D50 of the carbon-based silicon-tin-carbon composite materials in the embodiments and comparative examples was tested using a Malvern particle size tester.
[0138] The pore size was measured using a POROLUX Cito instrument.
[0139] Conductivity using Orion Star TM A212 conductivity benchtop meter is used for measurements at room temperature.
[0140] The results are shown in Table 1.
[0141] Table 1
[0142]
[0143]
[0144] Effect Example 2
[0145] The preparation method of the button cell used to test the electrochemical performance is as follows: the carbon-based silicon-tin-carbon composite material prepared in the embodiment and the comparative example is mixed evenly with a conductive agent (KS-6), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) at a ratio of 95.5:1.5:1.5:1.5, and applied on a copper foil with a compaction density of 1.60 g / cm 3 , vacuum dried as the negative electrode, lithium metal as the counter electrode, and 1M LiPF as the electrolyte 6 A mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 1:1, and a PE / PP / PE composite membrane are used as the separator, which can be assembled into a button battery.
[0146] The rebound of the pole piece made of the carbon-based silicon-tin-carbon composite material obtained in the above-mentioned embodiments and comparative examples was tested. The test method for the pole piece rebound is: the pole piece is baked and left to stand in an oven at 80°C for 0, 24, 48, 72, and 96 hours, and then the thickness of the pole piece is tested. The rebound rate of the pole piece at 24h = (the thickness of the pole piece at 24h - the thickness of the pole piece at 0h) / the thickness of the pole piece at 0h × 100%. The rebound rate of the pole piece at 96h = (the thickness of the pole piece at 96h - the thickness of the pole piece at 0h) / the thickness of the pole piece at 0h × 100%.
[0147] The internal resistance test method is: the assembled battery is cycled for one week at a rate of 0.1C, and then the electrochemical impedance spectroscopy (EIS) method (compacted density 1.65g / cm 3 ) to obtain the internal resistance, as shown in Table 2 below.
[0148] Table 2
[0149]
[0150]
[0151] The above button cell was subjected to various electrical performance tests on a blue battery tester, the test condition was 25°C, and the charging voltage limit was 0.005-2V.
[0152] (1) First discharge specific capacity and first coulombic efficiency
[0153] The charge and discharge were carried out at a rate of 0.1C, and the first discharge specific capacity and the first coulombic efficiency were tested. The test results are shown in Table 3.
[0154] (2) Cycle performance (200 cycles at 0.1C rate)
[0155] The charge and discharge cycles were performed 200 times at a rate of 0.1C, and the 200th discharge specific capacity was recorded as the 200th cycle retention capacity. The test results are shown in Table 3 and Figure 3 shown. Figure 3Schematic diagram of the cycle performance of the carbon-based silicon-tin-carbon composite material obtained in Example 1.
[0156] Table 3
[0157]
[0158]
[0159] The test conditions for rate performance are: rate charge and discharge at a current density of 0.1mA / g-2mA / g, and the charging voltage is limited to 0.005-2V. The rate performance (within 50 cycles) and cycle performance (within 200 cycles) are tested at a current density of 0.1mAh / g. The results are shown in Table 4 and Figure 4 . Figure 4 Schematic diagram of the rate performance of the carbon-based silicon-tin-carbon composite material obtained in Example 1.
[0160] Table 4
[0161] Rate performance 0.1C 99.87% 0.2C 88.73% 0.5C 85.67% 1.0C 78.98% 2.0C 65.32% 0.1C 98.79%
[0162] From Table 4 and Figure 3 It can be seen that after 0.1C / 0.2C / 0.5C / 1C / 2C cycles, the capacity of the battery assembled with the carbon-based silicon-tin-carbon composite material of Example 1 can still remain consistent with the initial rate when it is restored to 0.1C, indicating that the carbon-based silicon-tin-carbon composite material has good rate performance.
Claims
1. A carbon-based silicon-tin-carbon composite material, characterized in that: It includes a plurality of silicon-tin-carbon composite particles dispersed in a carbon substrate; the silicon-tin-carbon composite particles include a shell layer and tin-containing particles and nano-silicon particles encapsulated in the shell layer; The shell layer includes a tin-containing carbon layer.
2. The carbon-based silicon-tin-carbon composite material according to claim 1, characterized in that: The carbon-based silicon-tin-carbon composite material satisfies one or more of the following conditions (1)-(6): (1) In the silicon-tin-carbon composite particles, the silicon content is 10%-40%, preferably 16%-35%, for example, 33.8%, 24.1%, 23.6%, 23.2%, 22.8%, 22.4%, 22.2%, 22.1%, 21.9%, 21.8%, 21.5%, 21.4%, 21.1%, 20.9%, 20.8%, 20.7%, 19.9%, 19.3% or 18.1%; (2) In the silicon-tin-carbon composite particles, the tin content is 30%-60%, preferably 35%-55%, for example, 51.8%, 51.4%, 50.3%, 50.2%, 49.1%, 48.6%, 48.2%, 47.3%, 47.1%, 47.0%, 46.3%, 46.0%, 45.8%, 45.7%, 45.6%, 44.8%, 44.7%, 44.3%, 44.2%, 43.4% or 39.4%; (3) In the silicon-tin-carbon composite particles, the carbon content is 10%-30%, preferably 15%-25%, for example, 22.7%, 21.8%, 20.7%, 20.5%, 20.1%, 19.8%, 19.7%, 19.2%, 18.9%, 18.3%, 18.1%, 17.9%, 17.8%, 17.7% or 17.6%; (4) In the silicon-tin-carbon composite particles, the oxygen content is 4%-20%, preferably 6%-15%, for example, 14.1%, 12.9%, 12.7%, 12.3%, 11.9%, 11.7%, 11.2%, 10.8%, 10.4%, 9.9%, 9.8%, 9.7%, 9.3%, 8.8%, 8.3%, 8.2% or 7.5%; The content of each element above indicates the percentage of the mass of each element to the mass of the silicon-tin-carbon composite particles; (5) The shell layer is a tin-containing carbon layer doped with heteroatoms; Wherein, the type of the heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen; Wherein, in the silicon-tin-carbon composite particles, the content of the heteroatoms is preferably 0.01%-2%, more preferably 0.05%-1.5%, for example 1.00%, 0.09%, 0.08% or 0.07%; the content of heteroatoms represents the percentage of the mass of the heteroatoms to the mass of the silicon-tin-carbon composite particles; and, (6) The structure of the silicon-tin-carbon composite particles includes any one of the following: ① The shell layer includes a second shell layer, the second shell layer includes a silicon film layer, and the second shell layer is coated on the surface of the tin-containing carbon layer; ② The shell layer includes a second shell layer, the second shell layer includes a porous carbon layer, and the second shell layer is coated on the surface of the tin-containing carbon layer; ③ The shell layer includes a second shell layer and a third shell layer, the second shell layer includes a silicon membrane layer, and the third shell layer includes a porous carbon layer, and the second shell layer and the third shell layer are sequentially coated on the surface of the tin-containing carbon layer.
3. A method for preparing a carbon-based silicon-tin-carbon composite material as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: ball-milling and pyrolyzing the silicon-tin-carbon composite particles and the carbon source B.
4. The method for preparing the carbon-based silicon-tin-carbon composite material according to claim 3, characterized in that: The method for preparing the carbon-based silicon-tin-carbon composite material satisfies one or more of the following conditions (1)-(6): (1) The carbon source B is a sugar, more preferably one or more of sucrose, maltose and fructose, such as sucrose; (2) The mass ratio of the silicon-tin-carbon composite particles to the carbon source B is (0.5-2):1, for example 1:1; (3) The pyrolysis of the silicon-tin-carbon composite particles and the carbon source B is carried out under an inert atmosphere; the inert atmosphere is preferably argon, nitrogen, helium or neon, such as nitrogen; (4) The pyrolysis temperature is 350-700°C, for example 550°C; (5) the pyrolysis time is 2-5 hours, for example 3 hours; and, (6) The temperature is raised to a pyrolysis rate of 5-15°C / min, for example, 10°C / min.
5. A method for preparing silicon-tin-carbon composite particles, characterized in that: The method comprises the following steps: coating a carbon source including a tin-containing substance on the surface of a mixture of a tin source and a silicon source, and subjecting the mixture to carbonization treatment to obtain the silicon-tin-carbon composite particles.
6. The method for preparing silicon-tin-carbon composite particles according to claim 5, characterized in that: The method for preparing the silicon-tin-carbon composite particles satisfies one or more of the following conditions (1)-(9): (1) The type of the tin source is one or more of tributylphenyltin, tetraphenyltin, phenylacetyl tributyltin and dibutyldiphenyltin, for example, tributylphenyltin; (2) The silicon source is silicon powder and / or silicon oxide powder; the D50 of the silicon source is preferably 20-60 nm, for example 25 nm; (3) The molar ratio of the tin source to the silicon source is (0.8-3):1, preferably (1-2):1, for example 1.6:1; (4) the tin-containing substance is one or more of anhydrous tin chloride, stannous chloride, stannous sulfate and an organic acid / tin complex, such as anhydrous tin chloride and / or an organic acid / tin complex; (5) The carbon source is a phenolic resin and / or asphalt, preferably a surfactant-fixed phenolic resin, more preferably a surfactant-fixed tin-containing phenolic resin; (6) The carbonization treatment is carried out under an inert atmosphere; the inert atmosphere is preferably nitrogen or argon; (7) The temperature of the carbonization treatment is 550-850° C., for example, 600° C.; (8) the carbonization treatment time is 2-6 hours, for example 3 hours; and, (9) The method for preparing the silicon-tin-carbon composite particles further comprises any one of the following steps: ① ball milling and pyrolysis of the particles obtained after the carbonization treatment and the silane coupling agent; ② ball-milling and pyrolyzing the particles and sugars obtained after the carbonization treatment; ③ ball-milling the particles obtained after the carbonization treatment and the silane coupling agent to obtain composite particles A; ball-milling and pyrolyzing the composite particles A and sugars; Wherein, the silane coupling agent is preferably one or more of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(β-methoxyethoxy)silane and methacryloxysilane, such as vinyl triethoxysilane; Wherein, the mass ratio of the particles obtained after the carbonization treatment to the silane coupling agent is preferably (10-22):1, more preferably (12-18):1, for example 16:1; Wherein, the particles obtained after the carbonization treatment and the silane coupling agent are preferably pyrolyzed under an inert atmosphere; the inert atmosphere is preferably argon, nitrogen, helium or neon, such as nitrogen; the pyrolysis temperature is preferably 350-700°C, such as 550°C; the pyrolysis time is preferably 2-5h, such as 3h; the rate of heating to the pyrolysis is preferably 5-15°C / min, such as 10°C / min; Wherein, the type of sugar is preferably one or more of sucrose, maltose and fructose, such as sucrose; Wherein, the mass ratio of the particles obtained after the carbonization treatment to the sugar is preferably (0.5-2):1, for example 1:1; Among them, when the particles and sugars obtained after the carbonization treatment are pyrolyzed, it is preferably carried out under an inert atmosphere; the inert atmosphere is preferably argon, nitrogen, helium or neon, such as nitrogen; the pyrolysis temperature is preferably 350-700°C, such as 550°C; the pyrolysis time is preferably 2-5h, such as 3h; the rate of heating to the pyrolysis is preferably 5-15°C / min, such as 10°C / min.
7. The method for preparing silicon-tin-carbon composite particles according to claim 6, characterized in that: The method for preparing the silicon-tin-carbon composite particles satisfies one or more of the following conditions (1)-(3): (1) When the tin-containing substance is an organic acid / tin complex, the method for preparing the organic acid / tin complex comprises the following steps: reacting an organic acid solution with an inorganic tin source to obtain an organic acid / tin complex; Wherein, the type of organic acid in the organic acid solution is preferably one or more of citric acid, tartaric acid, malic acid and lactic acid, such as citric acid; the type of the inorganic tin source is preferably one or more of anhydrous tin chloride, stannous chloride and stannous sulfate, such as anhydrous tin chloride; the molar ratio of the organic acid to the inorganic tin source in the organic acid solution is preferably 1:(2.08-2.8), more preferably 1:(2.2-2.5), such as 1:2.33; during the reaction, the pH value of the reaction system is preferably monitored; the pH value of the reaction system is preferably not more than 12, such as 5-12; (2) When the carbon source is a phenolic resin, the method for preparing the carbon source of the tin-containing substance comprises the following steps: polymerizing the tin-containing substance, formaldehyde and resorcinol; Wherein, the molar ratio of the tin-containing substance to the resorcinol is preferably (0.5-2.5):1, more preferably (1-2):1, such as 1.6:1; the molar ratio of the formaldehyde to the resorcinol is preferably (333-3000):1, such as 1000:1; the temperature of the polymerization reaction is preferably 80-100°C, such as 85°C; the time of the polymerization reaction is preferably 2-6h, such as 3h; a catalyst is preferably added during the polymerization reaction; the catalyst is preferably an alkaline solution, such as a sodium carbonate solution, a sodium hydroxide solution or a sodium citrate solution; Alternatively, when the carbon source is a phenolic resin fixed by a surfactant, the method for preparing the carbon source of the tin-containing substance comprises the following steps: polymerizing the surfactant, the tin-containing substance, formaldehyde and resorcinol; Wherein, the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, such as hexadecyltrimethylammonium bromide; the molar ratio of the surfactant to the resorcinol is preferably (0.2-0.8):1, more preferably (0.4-0.6):1, such as 0.492:1; and, (3) The carbon source includes heteroatom doping; Wherein, the type of the heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen; when the type of the heteroatom is nitrogen, the type of the nitrogen source is preferably one or more of p-nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile), such as triethylamine; The molar ratio of the heteroatom to the tin source is preferably 1:(60-100), more preferably 1:(70-90), for example 1:
80.
8. A silicon-tin-carbon composite particle, characterized in that: The silicon-tin-carbon composite particles are prepared by the method for preparing the silicon-tin-carbon composite particles as described in any one of claims 4 to 7.
9. A pole piece, characterized in that: It includes the silicon-tin-carbon composite particles as described in claim 8, or the carbon-based silicon-tin-carbon composite material as described in claim 1 or 2.
10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of carbon-coated tin and tin-iron alloy lithium-ion battery negative electrode material
CN110336015A